A conditional mutant allele for analysis of Mixl1 function in the mouse. Issue 5 (13th March 2014) - Pulina, Maria V.; Sahr, Kenneth E.; Nowotschin, Sonja; Baron, Margaret H.; Hadjantonakis, Anna‐Katerina
Summary Mixl1 is the only member of the Mix/Bix homeobox gene family identified in mammals. During mouse embryogenesis, Mixl1 is first expressed at embryonic day (E)5.5 in cells of the visceral endoderm (VE). At the time of gastrulation, Mixl1 expression is detected in the vicinity of the primitive streak. Mixl1 is expressed in cells located within the primitive streak, in nascent mesoderm cells exiting the primitive streak, and in posterior VE overlying the primitive streak. Genetic ablation of Mixl1 in mice has revealed its crucial role in mesoderm and endoderm cell specification and tissue morphogenesis during early embryonic development. However, the early lethality of the constitutive Mixl1−/− mutant precludes the study of its role at later stages of embryogenesis and in adult mice. To circumvent this limitation, we have generated a conditional Mixl1 allele (Mixl1cKO) that permits temporal as well as spatial control of gene ablation. Animals homozygous for the Mixl1cKO conditional allele were viable and fertile. Mixl1KO/KO embryos generated by crossing of Mixl1cKO/cKO mice with Sox2‐Cre or EIIa‐Cre transgenic mice were embryonic lethal at early somite stages. By contrast to wild‐type embryos, Mixl1KO/KO embryos contained no detectable Mixl1, validating the Mixl1cKO as a protein null after Cre‐mediated excision. Mixl1KO/KO embryos resembled the previously reported Mixl1−/− mutant phenotype. Therefore, the Mixl1 cKO allele provides a tool for investigating the temporal and tissue‐specific requirements for Mixl1 in the mouse. genesis 52:417–423, 2014. © 2014 Wiley Periodicals, Inc.